An analysis of heat and mass transfer of ternary nanofluid flow over a Riga plate: Newtonian heating - Mahabaleshwar, U. S.; Nihaal, K. M.; Perez, L. M.; Öztop, Hakan Fehmi (Taylor & Francis Inc, 2025)
Ternary nanofluids have been show cased to substantially enhance the thermal conductivity and heat transfer attributes of base fluids when compared to ordinary fluids, nanofluids, and hybrid nanofluids. As expected, they are beneficial in thermal management and cooling, and other applications that require effective heat transference. The present analysis deals with the ternary nanofluid flow with heat transmission across Riga plate considering Newtonian heating effect. Fe2O4, ZnO, and CoFe2O4 are in a base fluid H2O creating a unique combination of Fe2O4-ZnO-CoFe2O4-H2O that offers various physical and chemical properties. Using appropriate similarity variables, the controlling PDEs are deformed to ODEs, that are analyzed via shooting method and byp4c algorithm. The consequences of several parameters are discussed Graphical on temperature, concentration, and velocity profiles are shown. The outcome of the present analysis shows that in the presence of a Newtonian heating effect, the temperature profile shows better thermal performance than in the absence of the Newtonian heating effect. Additionally, the nature of certain significant engineering coefficients for specific parameters is studied in this article. It is seen that the heat source elevates the rate of heat transfer between a solid surface and fluid flow, whereas opposite trend is observed when the heat sink is considered. Also, the rate of mass transfer is achieved by rising values of the chemical reaction parameter.
Keywords: Chemical reaction; inclined magnetic field; nonlinear heat/source sink; Newtonian heating; stagnation point; ternary nanofluid